A strong minimum principle and large time asymptotics for viscosity solutions to a class of doubly nonlinear possibly degenerate parabolic equations. (August 2022) - Bhattacharya, Tilak; Marazzi, Leonardo
Abstract: We study a version of the strong minimum principle, and large time asymptotics of positive viscosity solutions to classes of doubly nonlinear parabolic equations of the form H ( D u, D 2 u ) − u k − 1 u t = 0, k ≥ 1, in Ω × [ 0, T ), where Ω ⊂ R n is a bounded domain and 0 < T ≤ ∞ . The spatial operator H is homogeneous with power k .